The reality of implementing professional development programs for Jeddah Secondary Public Schools Female teachers and means to develop them in light of KSA’s 2030 Vision from Schools Leadership Supervisory Perspectives - Al- Saedy, Alya Abdullah; Hariri, Randa (Journal of Educational and Psychological Sciences, 2021)
This study aimed to discover the status of implementing the professional development programs for female school leaders in secondary public schools in Jeddah from the perspectives of school leadership supervisors as well as the means of improving these programs in light of 2030 Vision. The study adopted the mixed method research design and utilized the questionnaire as a tool to collect data from a sample of (22) school leaders’ supervisors. Findings revealed that secondary school leaders in Jeddah do apply professional development programs in relation to making decision and strategic planning domains in light of 2030 Vision at a moderate level. Also, findings revealed that the effectiveness of professional development programs for educational leaders at schools is manifested in these programs being participatory, have clear and systematic goals, continuous, enriching and sustainable. The study concluded with a recommendation to provide workshops and training programs to support the school leaders, and to encourage and motivate school leaders to continue to follow up on strategic planning practices on monthly and annual basis.